2009
DOI: 10.1002/ejic.200900239
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Insertion Reactivity, and Transmetalation Reactions of the Lithium Complex [{2‐(6‐R‐Pyr)(Me3Si)}CHLi·OEt2]2 (R = H or Me)

Abstract: Treatment of 6‐R‐2‐(Me3SiCH2)C5H3N (R = H or Me) with nBuLi in diethyl ether affords the dimeric lithium complexes [{2‐(6‐R‐Pyr)(Me3Si)}CHLi·OEt2]2 (Pyr = pyridine, C5H3N) in high yields. In these complexes, the two anionic ligands have different bonding modes. These complexes easily undergo insertion reactions with nitriles to form six‐membered cyclic dimeric complexes in good yields. Further transmetalations of the six‐membered cyclic complexes with CuCl, SnCl4, or CoCl2 allow the formation of new metal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The azaallyl alkali-metal compounds [5][6][7][8] were easily prepared by the coupling reaction of bis (trimethylsily)methylmetal compounds with α-H-free nitriles [9,10]. The first facial η 3 -azaallyl model was confirmed within [Li{μ-N(SiMe 3 ) C( t Bu)CH(SiMe 3 )}] 2 [10], whilst the first η 1 -fashion was observed in pyridyl-1-azaallyl-lithium, [(2-(6-R-Pyr)(Me 3 Si)CHLi·OEt 2 ] 2 [11]. The reaction of Li 2 {η 5 -C 5 H 4 Si(Me) 2 C(H)SiMe 3 } with t BuCN produced a silyl-bridged cyclopentadienyl-azaallyl-lithium [12].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The azaallyl alkali-metal compounds [5][6][7][8] were easily prepared by the coupling reaction of bis (trimethylsily)methylmetal compounds with α-H-free nitriles [9,10]. The first facial η 3 -azaallyl model was confirmed within [Li{μ-N(SiMe 3 ) C( t Bu)CH(SiMe 3 )}] 2 [10], whilst the first η 1 -fashion was observed in pyridyl-1-azaallyl-lithium, [(2-(6-R-Pyr)(Me 3 Si)CHLi·OEt 2 ] 2 [11]. The reaction of Li 2 {η 5 -C 5 H 4 Si(Me) 2 C(H)SiMe 3 } with t BuCN produced a silyl-bridged cyclopentadienyl-azaallyl-lithium [12].…”
Section: Introductionmentioning
confidence: 66%
“…The reaction of Li 2 {η 5 -C 5 H 4 Si(Me) 2 C(H)SiMe 3 } with t BuCN produced a silyl-bridged cyclopentadienyl-azaallyl-lithium [12]. Therefore there were various coordination within lithioorganic complexes such as η 5 -fashion of cyclopentadienyl [12], indenyl and fluorenyl [13], η 3 -allyllic [10,13a], η 1 -allyllic [11] and a few η 6 -arene [14,15]. In this work, the reaction of 9-trimethylsilylfluorenyllithium with α-hydrogen-free nitriles produced three organolithium compounds, and showed the bonding features of ligands as η 3 -fluorenyl, η 3 -azaallyl, η 6 -arene and donating bonds.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes are air and moisture sensitive, and they are soluble in aromatic hydrocarbons (benzene, toluene) except for complex 6b which is slightly soluble in toluene but readily soluble in THF. All aluminum complexes were characterized by 1 H and 13 C NMR spectroscopy and elemental analyses. Compared to ligands 1a-6a, the 1 H NMR spectra of 1b-6b showed no proton signals appearing in low field regions (δ 14.95 to 15.70 ppm) and the resonances for the protons of Al-CH 3 appeared in the high-field regions (δ −0.60 to −0.48 ppm).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Recently, Bildstein and his co-workers have synthesized pyridyl/chinolyl [N,O] β-ketiminato and [N,N] β-diketiminato ligands by modifying a literature procedure, which utilizes the reaction of picolyl/quinolyl-lithium with acetonitrile or benzonitrile followed by acidic hydrolysis. 12 We have reported that the insertion reaction of lithiated picoline with nitriles gives [N,N] β-diketiminato complexes 13 and lithium quinolylamide with nitriles affords quinolylguanidinates. 14 With this in mind, we decided to explore the preparation of aluminum derivatives coordinated by bidentate quinolylenolate ligands and to mediate as a catalyst in the polymerization of cyclic esters.…”
Section: Introductionmentioning
confidence: 99%
“…(Azaallyl)metal complexes have drawn much attention due to the diverse bonding modes of azaallyl groups such as the terminal κ 1 -enamido (I) and a monometallic (II) and bimetallic η 3 fashion (III) (Scheme ) . Numerous complexes of the main-group elements and transition metals have been explored. Our efforts have focused on the (η 3 -azaallyl)zirconium complexes because of the great potential of zirconium complexes in producing polyolefins with unique properties .…”
Section: Introductionmentioning
confidence: 99%